'Radical Orthodoxy' and debating the foundations of the legal protection of religious liberty - Harrison, JT (2015)
This thesis examines the rationale for religious liberty in England and Wales. Currently, United Kingdom religious liberty literature shows very little sustained interrogation of the topic. Authors are likely to assume religious liberty is, most notably, a species of personal autonomy. This fails to explain why we should care about religious liberty and deepens religion’s privatisation, its separation from politics or public life. Drawing from a theological sensibility known as Radical Orthodoxy (RO), this thesis criticises current assumptions and argues that religious liberty discourse should be re-envisioned. The Introduction and Chapter One explore the current problems facing religious liberty discourse and map rationales given by prominent authors. Chapter Two argues that the main problem is that current discourse is shaped by a secularisation narrative: the differentiation of religious and secular spheres. Chapter Three relates the RO argument that this differentiation is underpinned by three themes, all of which have theological components: the rise of secular order as the protection of individual rights; the invention of private religion in modernity; and the contemporary shift to 'authenticity' or diffuse individual experiences as the hallmark of religion. Chapter Four contends that these three themes are echoed in religious liberty discourse and jurisprudence, leaving us with the question of why religious liberty matters. Chapters Five and Six explore the RO-influenced alternative, in theory and with reference to common questions in religious liberty discourse: the relationship between an individual claimant and the group; the reality of plural religious traditions; and the tension between sexual orientation non-discrimination and religious liberty. On the RO-influenced account, religious liberty concerns, against sphere differentiation, a commitment to the flourishing of multiple groups contributing to desirable social ends, understood ultimately as participating in the life of 'charity', the love of God and of others. This encapsulates two themes, both rooted in the Christian tradition: judgement against politics (as reflected in the secular order), and transformation of society along social pluralist lines. These two themes, the thesis argues, better explain why religious liberty matters.